THE POTENTIALS AND CHALLENGES OF MOBILE-ASSISTED LANGUAGE LEARNING (MALL) FOR EFL/ESL LEARNERS - Sanjaya, Eko (LPPM IKIP PGRI Pontianak, 2023)
Mobile-assisted Language Learning (MALL) studies have indicated promising potentials for English language learning enhancement. However, since the implementation of MALL can be viewed as the process of transition from physical learning to e-learning, the implementation has also faced challenges in real practices. Thus, this study aims to review the opportunities and challenges that have been experienced by EFL/ESL learners in the implementation of MALL. Using descriptive qualitative method, the study was done by employing library research to collect the data. The study reviewed 30 publications in the MALL implementation area. The data were analyzed based on the reported potentials and challenges in the MALL implementation. They were then categorized into the subthemes describe the potentials and challenges. The findings showed a variety of benefits and issues in MALL implementation.